Analysis of socioeconomic gradients in the development of children aged 0-3 years in Fortaleza, Northeastern Brazil - Florencia Lopez Boo; Mayaris Cubides Mateus; Suzanne Duryea (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To identify the socioeconomic gradients in the measures of development and well-being of children under three years of age in Fortaleza, Northeastern Brazil. METHODS We compiled information using a socioeconomic survey instrument, collecting anthropometric measurements, observing the home environment, and applying the Denver Test II to 2,755 children aged between zero and 28 months who are potential beneficiaries of the Cresça com Seu Filho program in Fortaleza. These children were randomly selected from a universe identified from the administrative record of the Cadastro Único of the Ministry of Social Development of Brazil. For the analysis, we reported descriptive statistics, Pearson correlations, and mean differences. RESULTS Rates of chronic malnutrition and overweight were 7.0%. The results of the Denver II test indicated that personal social (23%) and language (20%) are the domains in which children have the highest developmental delay, when compared with the international reference sample. Parental practices measured by two sub-scales of the Home Observation of the Environment Inventory were poor, with only 14.0% of families having two or more books in the home and 35.0% of the households reporting having spanked their child in the past three days. CONCLUSIONS We identified clear socioeconomic gradients in the anthropometric indicators, parenting practices, and the Denver Test II (especially in the language domain). Children from poorer households, as well as children of mothers with lower education levels, perform poorly on most measures.